Triple-Negative Breast Cancer Risk Genes Identified by Multigene Hereditary Cancer Panel Testing. (7th August 2018) - Shimelis, Hermela; LaDuca, Holly; Hu, Chunling; Hart, Steven N; Na, Jie; Thomas, Abigail; Akinhanmi, Margaret; Moore, Raymond M; Brauch, Hiltrud; Cox, Angela; Eccles, Diana M; Ewart-Toland, Amanda; et al.
Abstract: Background: Germline genetic testing with hereditary cancer gene panels can identify women at increased risk of breast cancer. However, those at increased risk of triple-negative (estrogen receptor–negative, progesterone receptor–negative, human epidermal growth factor receptor–negative) breast cancer (TNBC) cannot be identified because predisposition genes for TNBC, other than BRCA1, have not been established. The aim of this study was to define the cancer panel genes associated with increased risk of TNBC. Methods: Multigene panel testing for 21 genes in 8753 TNBC patients was performed by a clinical testing laboratory, and testing for 17 genes in 2148 patients was conducted by a Triple Negative Breast Cancer Consortium (TNBCC) of research studies. Associations between deleterious mutations in cancer predisposition genes and TNBC were evaluated using results from TNBC patients and reference controls. Results: Germline pathogenic variants in BARD1, BRCA1, BRCA2, PALB2, and RAD51D were associated with high risk (odds ratio > 5.0) of TNBC and greater than 20% lifetime risk for overall breast cancer among Caucasians. Pathogenic variants in BRIP1, RAD51C, and TP53 were associated with moderate risk (odds ratio > 2) of TNBC. Similar trends were observed for the African American population. Pathogenic variants in these TNBC genes were detected in 12.0% (3.7% non- BRCA1/2 ) of all participants. Conclusions: Multigene hereditary cancer panel testing can identify women with elevated risk of TNBC due to mutations in BARD1, BRCA1, BRCA2, PALB2, and RAD51D . These women can potentially benefit from improved screening, risk management, and cancer prevention strategies. Patients with mutations may also benefit from specific targeted therapeutic strategies.